2005
DOI: 10.1063/1.1901804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gold coating on local oxidation using an atomic force microscope

Abstract: A simple method to enhance atomic force microscopy local oxidation by coating the substrate with a thin layer of gold is reported. The effect of gold coating is demonstrated experimentally by atomic force microscopy oxidation at various thicknesses of gold on Si and InP. Oxide heights reaching 30nm are easily achieved on silicon at rates 10 times greater than traditional methods. The gold layer is assumed to increase conductance and current during oxidation, thereby reducing decline in growth rates caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…6,8,15 By coating the silicon surface with gold, Hwang et al have been able to increase the current flow of the circuit and thereby create oxides of up to 30 nm. 13,16 It has also been shown that increasing the ambient humidity of the system increases the size of the tip-surface capillary bridge and greatly enhances the oxide growth rate by providing a source of oxyanions and improving the conductivity of the circuit. 9,17,18 Nevertheless, the features in Figs.…”
Section: Resultsmentioning
confidence: 98%
“…6,8,15 By coating the silicon surface with gold, Hwang et al have been able to increase the current flow of the circuit and thereby create oxides of up to 30 nm. 13,16 It has also been shown that increasing the ambient humidity of the system increases the size of the tip-surface capillary bridge and greatly enhances the oxide growth rate by providing a source of oxyanions and improving the conductivity of the circuit. 9,17,18 Nevertheless, the features in Figs.…”
Section: Resultsmentioning
confidence: 98%
“…Semiconductor surfaces other than Si, such as GaAs 4 and GaN 5 have also been tried out. Supported films of metals on Si such as Au/Si, 6 Mo/Si, 7 Ti/Si 8 and Cr/Si 9 are examples of modified surfaces. In general, oxidation of the overlayer is observed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, atomic force microscopy-based local oxidation lithography (AFM-LO) techniques have been receiving increasing attention as attractive, emerging lithography techniques for fabrication of nano-scale patterns and related device structures [ 5 - 7 ]. Although electron beam and nano-imprint lithography techniques have been widely studied, there are issues with regard to the damage to structures caused by high-energy electron beams or high imprinting temperatures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%